2013
DOI: 10.7322/jhgd.50397
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Cardiac Autonomic Regulation and Auditory Mechanisms: Importance for Growth and Development

Abstract: Journal of Human Growth and Development 2013; 23(1): 94-98 ORIGINAL RESEARCH INTRODUÇÃOA música sempre fez parte de diversas culturas da humanidade, estabelecendo ligação entre sensações e prazeres humanos e sentidos, através da melodia e do ritmo. No entanto, com o abuso da intensidade, duração e / ou frequência da música, esse ruído pode se tornar um problema para audição 1 . A perda auditiva induzida por ruído é bem conhecida por estudos relacionados com o ambiente de trabalho. Por outro lado, há uma cres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
20
0
2

Year Published

2014
2014
2016
2016

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 37 publications
0
20
0
2
Order By: Relevance
“…We did not include subjects with previous experience with music instrument and classic ballet music, as well as volunteers which like heavy metal and classical music styles, since it affects cardiovascular responses [12]. …”
Section: Methodsmentioning
confidence: 99%
“…We did not include subjects with previous experience with music instrument and classic ballet music, as well as volunteers which like heavy metal and classical music styles, since it affects cardiovascular responses [12]. …”
Section: Methodsmentioning
confidence: 99%
“…[6] Although it has been reported the beneficial effects of musical auditory stimulation for a long period of time, [7] the short-term effects of classical musical auditory stimulation on cardiac autonomic regulation is not a consensus. [1][2][3]8,9] We hypothesized that auditory stimulation with classical baroque music influences the cardiac autonomic responses to the PCM. Therefore, we aimed to evaluate the acute effects of classical baroque music on the cardiac autonomic responses induced by the PCM in healthy women.…”
Section: Introductionmentioning
confidence: 99%
“…The relationship between the auditory and cardiovascular systems is based on common areas in the brain that regulate the both systems. [1,2] A previous study…”
mentioning
confidence: 97%
“…Relaxant music has been reported to present positive influence on stress reduction, relaxation, pain management, neural cognition and cardiac function [2,3]. Auditory stimulation with music is known to induce several psychological responses, leading to changes in the autonomic nervous system [4,5].In this context, the heart rate variability (HRV) is a non-invasive method that evaluates the cardiac autonomic control in humans, it is a conventionally accepted term to describe the fluctuations in the intervals between consecutive heart beats (RR intervals), which are related to the influences of the ANS on the sinus node [6].Great part of studies has observed the relaxing effect of classical music. On the other hand, genres such as heavy metal, hip hop and techno music are commonly associated with physiologic excitement [7].…”
mentioning
confidence: 99%
“…Relaxant music has been reported to present positive influence on stress reduction, relaxation, pain management, neural cognition and cardiac function [2,3]. Auditory stimulation with music is known to induce several psychological responses, leading to changes in the autonomic nervous system [4,5].…”
mentioning
confidence: 99%